Role of Subvoxel Free Fluid on Diffusion Parameters in Brain Tissue with Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy and Its Correlation with Physical Disability: Histogram Analysis of Standard and Fluid-Att… - Dichgans, Martin; Pütz, Benno; Boos, Daniel; Auer, Dorothee P. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Subcortical signal intensity abnormalities and lacunar infarcts are the radiologic hallmark of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy. MR diffusion studies reveal abnormalities in lesions and also within normal appearing white matter. To further characterize the underlying pathologic abnormality, we evaluated the role of subvoxel free fluid in brain with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy on diffusion parameters and physical disability and analyzed the interrelation between diffusion variables and nonlacunar T2 lesion load.METHODS: Mean diffusivity maps from fluid-attenuated and standard diffusion images of 13 patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy and seven age-matched control participants were compared by means of histogram analysis for three tissue compartments (whole brain parenchyma, normal appearing brain tissue, and nonlacunar lesions) by using a semiautomated region growing algorithm to define whole brain parenchyma and lesions on fluid-attenuated images.RESULTS: In both patients and control participants, the average mean diffusivity of whole brain parenchyma was lower on fluid-attenuated than on standard images (P < .001). Average mean diffusivity and peak location for all compartments were significantly elevated in patients (P < .001) and higher for lesions than for normal appearing brain tissue on both types of images (P < .001). The difference between standard and fluid-attenuated average mean diffusivity of normal appearing brain tissue, reflecting the subvoxel free fluid content, was elevated in patients (P < .05) and correlated closely with the Rankin score (Spearman’s rank correlation coefficient = 0.889, P < .001). Average mean diffusivity of whole brain parenchyma and normal appearing brain tissue correlated strongly with the nonlacunar T2 lesion load (Pearson’s correlation coefficient = 0.743–0.928, P < .005).CONCLUSION: This study shows that standard diffusion measurements are contaminated by free fluid partial volume effects for patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy and for control participants. It also provides evidence of a clinical significance of increased subvoxel free fluid in normal appearing brain with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, which may be more important than either global atrophy, increased diffusivity or, T2 lesion load.